Impactos do Crédito Rural no mercado de trabalho da agropecuária dos estados brasileiros - Silva, João Paulo Rios e (2018)
This research analyses the repercussions of rural credit on agricultural labour market of Brazilian states, particularly on wages and employment level of this sector. For this a panel data was built with information on real wages, formal jobs criated, rural credit and agricultural GDP between 2002-2015 for all 26 brazilian states. Evidence was withdrawn from cumulative impulse response functions obtained from Panel Vector Autoregressive (PVAR) models. The results indicated that real wages and agricultural GDP respond positively to shocks in rural credit and that, under similar conditions, the employment level presents a slightly reduction in the aggregate model. However, considering models for regional subsamples, there is evidence of positive impacts of agricultural credit on employment in the states of the North and Northeast regions, with labor-intensive farming, whereas negative repercussions on employment were found in Midwest, South and Southeast states, wich are more capital intensive.